2020
DOI: 10.3390/nu12113277
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Absorption in Intestinal Cells: Evidence of Cross-Talk between EGF and TRPM6 and Novel Implications for Cetuximab Therapy

Abstract: Hypomagnesemia is very commonly observed in cancer patients, most frequently in association with therapy with cetuximab (CTX), a monoclonal antibody targeting the epithelial growth factor receptor (EGFR). CTX-induced hypomagnesemia has been ascribed to renal magnesium (Mg) wasting. Here, we sought to clarify whether CTX may also influence intestinal Mg absorption and if Mg supplementation may interfere with CTX activity. We used human colon carcinoma CaCo-2 cells as an in vitro model to study the mechanisms un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Some anticancer drugs, including cisplatin (CDDP), a platinum based anticancer drug, and cetuximab and panitumumab, chimeric and fully human monoclonal antibodies to the epidermal growth factor receptor (EGFR), often cause a side effect of hypomagnesemia [ 5 ]. Cetuximab downregulates TRPM6-mediated Mg 2+ influx by interfering with EGF signaling [ 6 ]. In addition, anti-EGFR agents induce kidney and cardiac disorders [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some anticancer drugs, including cisplatin (CDDP), a platinum based anticancer drug, and cetuximab and panitumumab, chimeric and fully human monoclonal antibodies to the epidermal growth factor receptor (EGFR), often cause a side effect of hypomagnesemia [ 5 ]. Cetuximab downregulates TRPM6-mediated Mg 2+ influx by interfering with EGF signaling [ 6 ]. In addition, anti-EGFR agents induce kidney and cardiac disorders [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypomagnesemia is frequently associated with EGFRI treatment because the blocking of the activation of EGFRs decreases the expression of transient receptor potential melastatin 6 (TRPM6) regulating the absorption and reabsorption of magnesium in the intestine and renal tubules 8,9 . In this study, we found that serum zinc and magnesium levels were significantly correlated.…”
Section: Discussionmentioning
confidence: 72%
“…EGFRI treatment, especially anti‐EGFR monoclonal antibodies, is known to decrease serum magnesium levels 8,9 . Serum magnesium levels were measured in 15 of the 16 patients treated with anti‐EGFR antibodies, and the mean ± SD of serum magnesium levels was 1.6 ± 0.27 mg/dL (normal range 1.8–2.5 mg/dL).…”
Section: Resultsmentioning
confidence: 99%
“…In line with the role of EGF signalling in TRPM6 activation, hypomagnesemia is a common side effect of treatment with the EGFR antibody cetuximab, occurring in 20-30 % of the patients (18,91,92) . Cetuximab prevents the EGF-induced activation of TRPM6 in kidney and colon cells, indicating the hypomagnesemia can be attributed to a decrease in both renal and intestinal (re)absorption (18,93) . Hypomagnesemia is not reported in patients treated with EGFR TKI (94) .…”
Section: Luminal Mg 2+ Uptake In the Intestine And Distal Convoluted Tubulementioning
confidence: 99%